PENGARUH PAD, DAK, SILPA TERHADAP BELANJA MODAL PADA PEMERINTAHAN KABUPATEN/KOTA DI PROVINSI ACEH - Riskan, Muhammad Azis; Meutia, Rita; Afrianandra, Cut (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2024)
The study aims to examine the influence of Local Own-Source Revenue (PAD), Special Allocation Fund (DAK), and Budget Surplus (SILPA) on Capital Expenditures in districts/cities in Aceh Province for the years 2019-2022. This research is quantitative with the population of all districts/city governments in Aceh with a total of 23 local governments. The sampling technique used is a census where the entire research population becomes a research sample. The data used is secondary data obtained from the Budget Realization Report listed in the Audit Report on the Regional Government Financial Statements. Data analysis uses a multiple linear regression analysis method with the help of SPSS 27. In this study, the results of PAD, DAK, and SILPA simultaneously have a positive and significant effect on capital expenditures in districts/cities in Aceh Province. PAD has partially had no positive effect on capital expenditures in districts/cities in Aceh Province. DAK and SILPA partially have a positive effect on capital expenditures in districts/cities in Aceh Province.